REALISASI KESANTUNAN PADA ACARA TALK SHOW “MATA NAJWA” - Widya Gusvita (Riksa Bahasa, 2016)
This study aimed to describe the use of politeness language in the communication process in the mass media television. The process of communication is not only considering the language according to the rules of grammar, but also got to see decency and civility in its use. The method used in this research is qualitative descriptive. The data collection technique used is the technique see and record. The data analysis technique used is dishonest. Source of research data be recorded impressions talk show "Mata Najwa" with guest stars Habibie. This research data is a speech containing the implementation and violations of politeness maxims, either to obey or violate the principle of politeness. Researcher found the number of terms of carrying and violations of politeness maxims there are 54 data. From these data, speech containing the implementation of as many as 38 pieces, and a speech containing 16 pieces violations.